The Wind in the Willows - Grahame, Kenneth, 1859-1932.; Milne, A. A. 1882-1956. (Alan Alexander) (Philadelphia : Courage Books, 1994)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
Keywords: Animals -- Fiction